Cinnamaldehyde attenuates streptozocin-induced diabetic osteoporosis in a rat model by modulating netrin-1/DCC-UNC5B signal transduction - Ji, Songjie; Zhao, Bingjia; Gao, Yuan; Xie, Jun; Han, Huijun; Wu, Qunli; Yang, Dan (Frontiers in Pharmacology, 2024)
Background: Cinnamaldehyde (CMD) is a major functional component of Cinnamomum verum and has shown treatment effects against diverse bone diseases. This study aimed to assess the anti-diabetic osteoporosis (DOP) potential of diabetes mellitus (DM) and to explore the underlying mechanism driving the activity of CMD. Methods: A DOP model was induced via an intraperitoneal injection of streptozocin (STZ) into Sprague–Dawley rats, and then two different doses of CMD were administered to the rats. The effects of CMD on the strength, remodeling activity, and histological structure of the bones were assessed. Changes in the netrin-1 related pathways also were detected to elucidate the mechanism of the anti-DOP activity by CMD. Results: CMD had no significant effect on the body weight or blood glucose level of the model rats. However, the data showed that CMD improved the bone strength and bone remodeling activity as well as attenuating the bone structure destruction in the DOP rats in a dose-dependent manner. The expression of netrin-1, DCC, UNC5B, RANKL, and OPG was suppressed, while the expression of TGF-β1, cathepsin K, TRAP, and RANK was induced by the STZ injection. CMD administration restored the expression of all of these indicators at both the mRNA and protein levels, indicating that the osteoclast activity was inhibited by CMD. Conclusions: The current study demonstrated that CMD effectively attenuated bone impairments associated with DM in a STZ-induced DOP rat model, and the anti-DOP effects of CMD were associated with the modulation of netrin-1/DCC/UNC5B signal transduction.